2017
DOI: 10.1038/s41598-017-15787-7
|View full text |Cite
|
Sign up to set email alerts
|

Self-righting potential and the evolution of shell shape in Galápagos tortoises

Abstract: Self-righting, the capacity of an animal to self-turn after falling on its back, is a fitness-related trait. Delayed self-righting can result in loss of mating opportunities or death. Traits involved in self-righting may therefore be under selection. Galápagos giant tortoises have two main shell morphologies - saddleback and domed – that have been proposed to be adaptive. The more sloped shape on the sides of the shell and the longer extension of neck and legs of the saddlebacks could have evolved to optimize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
(47 reference statements)
1
22
0
Order By: Relevance
“…The differences in the scutes from the left and right sides are consistent with the data obtained by many other researches performed in turtles and tortoises (Davis & Grosse, 2008;Macchi et al, 2008;Buică & Cogălniceanu, 2013;Cherepanov, 2014;Claude, 2016). Self-righting, the capacity of an animal to self-turn after falling on its back, which is a fitness-related trait (Domokos & Varkonyi, 2008;Chiari et al, 2017), is rejected, as no correlation was observed between extracted size and residual shape variables, as it would be logical if the FA had a this functional sense. The possibility of being a secondary sexual characters is also rejected, although being different between males and females, as it would need to appear with a negative relationship (larger sexual traits are presumably more costly to produce, which should lead to greater developmental stress and corresponding increases in asymmetry) (Jennions, 1996).…”
Section: Discussionsupporting
confidence: 89%
“…The differences in the scutes from the left and right sides are consistent with the data obtained by many other researches performed in turtles and tortoises (Davis & Grosse, 2008;Macchi et al, 2008;Buică & Cogălniceanu, 2013;Cherepanov, 2014;Claude, 2016). Self-righting, the capacity of an animal to self-turn after falling on its back, which is a fitness-related trait (Domokos & Varkonyi, 2008;Chiari et al, 2017), is rejected, as no correlation was observed between extracted size and residual shape variables, as it would be logical if the FA had a this functional sense. The possibility of being a secondary sexual characters is also rejected, although being different between males and females, as it would need to appear with a negative relationship (larger sexual traits are presumably more costly to produce, which should lead to greater developmental stress and corresponding increases in asymmetry) (Jennions, 1996).…”
Section: Discussionsupporting
confidence: 89%
“…But so too do island giant species such as Aldabrachelys or members of the Chelonoidis nigra complex (which can experience selection for self‐righting as adults (Chiari et al. )), and they do not occur particularly close to the unoccupied optima. These species are all closer to peaks with higher weights for strength–perhaps juvenile predation places selective pressure on juvenile shell shape, constraining potential adult shapes.…”
Section: Discussionmentioning
confidence: 99%
“…Certain shell shapes are thought to facilitate self-righting and reduce the energy required to successfully flip (Ashe, 1970), but the ability to self-right is important for all species of turtle. By integrating biomechanical data with morphological comparisons, it may be possible to identify traits that enable turtles to self-right despite morphological constraints (Chiari et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Turtles use a variety of strategies that are thought to be primarily dependent on shell morphology, which itself is strongly correlated with the habitat in which a species lives. In terrestrial taxa such as tortoises, the carapace (top of the shell) is typically domed, and turtles use a strategy primarily involving movements of the limbs to shift the center of mass and induce rolling of the body (Ashe, 1970;Chiari et al, 2017). However, in aquatic species with a flatter, more streamlined carapace, structures such as the limbs and head (though typically not the tail, which is reduced in most turtles) may be able to reach the ground and act as levers to flip the body (Ashe, 1970).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation